The Problem of Reduced Nicotinamide Adenine Dinucleotide Oxidation in Glyoxysomes - Lord, J. M. (1972)
NADH is generated in glyoxysomes both in the glyoxylate cycle and in β-oxidation. No system has yet been described which would oxidize NADH in these organelles. A series of oxidants which might function by coupling NADH oxidation to O(2) through endogenous carriers in the glyoxysomes was examined. Oxidation was brought about by ferricyanide or dichlorophenol-indophenol, but it was shown that this “diaphorase” activity is probably a contaminant. Hydroxypyruvate reductase (NAD-linked) is present in the glyoxysomes, and at very high substrate concentrations (>10 mm) this enzyme can also transfer electrons from NADH to glyoxylate. However, it is most unlikely that this concentration of glyoxylate is ever approached in glyoxysomes, where the malate synthetase would compete on much superior terms. The maximum rates of NADH oxidation observed in the presence of ferricyanide or glyoxylate are only a fraction of those required to reoxidize NADH at the rate occurring in vivo.